AWS Certified Solutions Architect (Associate) : complete video course - Jones, Richard A. (LiveLessons (Indianapolis, Ind.), 2018)
More than six hours of video instruction covering the knowledge necessary to pass the AWS Solutions Architect Associate certification exam, including an in-depth review of AWS architecture principles and best practices, and technical details pertaining to the implementation of services in accordance with the Well Architected Framework as published by Amazon Web Services. The AWS Certified Solutions Architect Associate Complete Video Course was developed specifically for the latest edition of the exam released in February of 2018. The AWS Solutions Architect Associate certification is ideal for anyone in a solutions architect or similar technical role, and this course is designed to help you pass the AWS Certified Solutions Architect Associate exam. We will cover all the key areas addressed in the exam and review a number of use cases designed to help you ingrain the principles and practices on which this certification is based so that you have an intellectual framework with which to formulate the correct answers. We will use a combination of demonstrations, architectural diagram walkthroughs, and case studies to help you understand the tools available to you for passing the exam. Throughout this course you will gain a deeper understanding of AWS architecture following the five pillars of the Well-architected framework. Demonstrations of Amazon Web Services and third-party cloud solutions are included to provide a clear guide to understanding the services offered by Amazon Web Services and the needs those services meet. Quizzes are also offered to help viewers gauge their ability to understand and retain the information presented.